An investigation of artificial intelligence (AI) literacy competency for library and information science (LIS) students in China - Ba, Xi; Hussin, Nurussobah; Kamarudin, Hanis Diyana (Faculty of Information Management, 2025)
Artificial intelligence is driving a new industrial revolution sweeping all aspects of human life, including technology, economy, science, politics, and art, like an unstoppable wave. This paper adopts a literature analysis methodology and extensively searches Chinese and foreign academic databases to analyse the relevant literature. A set of dimensions for AI literacy among LIS undergraduates has been developed in four first-level dimensions (AI knowledge, AI skills, AI attitude, AI ethics) and twelve second-level dimensions. Finally, this paper proposes continuing in-depth research on AI literacy and joining forces with multiple parties to promote universal education in AI literacy skills.